Deixis in Prabowo’s Religious-Themed Speeches: A Pragmatic Analysis - Muhamad Safi'i (International Journal of English and Applied Linguistics (IJEAL), 2025)
In the context of Indonesian political communication, affecting public opinion and attracting supports can be achieved by employing religious rhetoric. Religious references are commonly used by politicians to attract various audiences. However, the specific linguistic strategies used to achieve this effect remain underexplored, particularly the use of deictic expressions which focus on words and phrases that rely on contextual information for interpretation. This study addresses this gap by studying how Prabowo Subianto, the president of Indonesia and a significant Indonesian political figure, uses deixis in his religious-themed speeches to foster solidarity, assert leadership, and construct ideological narratives. The investigation employs pragmatic theory, particularly Levinson (1983) typology of deixis, which includes person, spatial (place), temporal (time), social, and discourse deixis. This study uses a qualitative descriptive method to analyze five of Prabowo’s speeches in order to identify the deictic expressions and their communicative functions. The findings of this study reveal a consistent use of inclusive person deixis (e.g., “kita”), spatial deixis that connects the audience in shared spaces, and temporal deixis that expresses urgency and collective momentum. Social deixis reflects politeness norms and cultural hierarchy in Indonesia, while discourse deixis ensures cohesion and rhetorical clarity. According to these findings, deixis in political speech can be considered instrumental, not merely referential, in maintaining relationships, expressing shared identity, and reinforcing ideological commitments. The implications suggest that deictic analysis offers an influential perspective for understanding the interaction of language, religion, and politics in Indonesian public discourse.